Transcriptome profiling based on protein–protein interaction networks provides a set of core genes for understanding the immune response mechanisms of the egg-protecting behavior in Octopus ocellatus. Issue 117 (October 2021) - Li, Zan; Bao, Xiaokai; Liu, Xintian; Li, Yan; Cui, Mingxian; Liu, Xiumei; Li, Bin; Feng, Yanwei; Xu, Xiaohui; Sun, Guohua; Wang, Weijun; Yang, Jianmin
Abstract: Protection via of the immune system is indispensable to the life of organisms. Within an immune network, problems with a given link will affect the normal life activities of the organism. Octopus ocellatus is cephalopod widely distributed throughout the world's oceans. Because of its unique nervous system and locomotive organs, research on this species has gradually increased in recent years. Many immune response mechanisms associated with behaviors of O. ocellatus are still unclear. Moreover, as a factor affecting the normal growth of O. ocellatus, egg protection has rarely been considered in previous behavioral studies. In this study, we analyzed the transcriptome profile of gene expression in O. ocellatus larvae, and identified 5936 differentially expressed genes (DEGs). GO and KEGG enrichment analyses were used to search for immune-related DEGs. Protein–protein interaction networks were constructed to examine the interactions between immune-related genes. Fifteen hub genes involved in multiple KEGG signaling pathways or with multiple protein–protein interaction relationships were obtained and verified by quantitative RT-PCR. We first studied the effects of egg protection on the immunity of O. ocellatus larvae by means of protein–protein interaction networks, and the results provide valuable genetic resources for understanding the immunity of invertebrate larvae. The data serve as a foundation for further research on the egg-protecting behavior of invertebrates. Highlights: This study is the first to represent the transcriptome analysis based on protein interaction network in cephalopods. It provides valuable gene resources for further study of the immune responses in invertebrate larvae. The data serve as a foundation for further research on the egg-protecting behavior of invertebrates.